Mediterranean Diet and Particulate Matter Exposure Are Associated With LINE-1 Methylation: Results From a Cross-Sectional Study in Women - Barchitta, Martina; Maugeri, Andrea; Quattrocchi, Annalisa; Barone, Germana; Mazzoleni, Paolo; Catalfo, Alfio; De Guidi, Guido; Iemmolo, Maria Giovanna; Crimi, Nunzio; Agodi, Antonella (Frontiers in Genetics, 2018)
Emerging evidence suggests that air pollution increases the risk of cardiovascular disease (CVD) and metabolic disorders, adding to the global burden of disease attributable to lifestyle and behavioural factors. Although LINE-1 methylation has been associated with these disorders, no studies have simultaneously examined the effects of diet and air pollution exposure on DNA methylation. Herein, we evaluated the association of particulate matter (PM with aerodynamic diameters of less than 10mm) exposure and adherence to Mediterranean Diet (MD) with LINE-1 methylation. Healthy women (n=299), aged 15 to 80 years, were enrolled in a cross-sectional study. Dietary data and adherence to MD were assessed by a Food Frequency Questionnaire (FFQ) and Mediterranean Diet Score (MDS). PM10 levels during one-month before recruitment were recorded by monitoring stations and assigned to each woman based on their residential address and day of recruitment. LINE-1 methylation in blood samples was assessed by pyrosequencing and reported as percentage of 5-Methylcytosine (5mC). The Mann–Whitney U test, Spearman's rank correlation test and linear regression models were applied. Our results demonstrated, for the first time, an inverse association between adherence to MD and exposure to PM10 with LINE-1 methylation: while higher monthly PM10 exposure decreases LINE-1 methylation level (β = -0.121; p= 0.037), the adherence to MD increases it (β = 0.691; p<0.001). MDS seemed to interact with PM10 levels (p=0.002) on LINE-1 methylation, as such we confirmed that the effect of MD decreased with increasing PM10 levels (β = 0.657; p<0.001 in the 1st tertile; β = 0.573; p<0.001 in the 2nd tertile; β = 0.551; p<0.001 in the 3rd tertile). Thus, we suggest that LINE-1 methylation is a possible mechanism underpinning environment-related health effects, and encourage further research to evaluate whether the adherence to the MD could counteract the negative effect of PM10 exposure. .